Juridical Review of the Transformation of the Pledge Concept into a Bullion Bank by PT Pegadaian Indonesia Based on FSA Regulation Number 17 of 2024 - Rechta Yoga Pratama; Nourma Dewi; Yulian Dwi Nurwanti (CV. Social Politic Genius (SIGn), 2026)
Macroeconomic dynamics drive the ontological transformation of gold from a mere static physical security to a digital-scale active financial instrument. This shift is legitimized by Law Number 4 of 2023 and FSA Regulation Number 17 of 2024, which grant PT Pegadaian authority to operate as a Bullion Bank. This research aims to analyze the juridical transformation of the pledge concept into Bullion Bank services and to evaluate the legal implications and customer protection vulnerabilities. This normative legal research utilizes the statute and conceptual approaches, which are analyzed prescriptively through grammatical and systematic interpretations of this legal relationship shift. The research results confirm that PT Pegadaian has essentially executed an intermediation function identical to banking through the unallocated account scheme. However, this authority expansion triggers legal implications, including potential disharmony with sectoral commodity trade regulations, threats of intellectual property disputes over the database system, and unpreparedness of the global standard-compliance infrastructure. The most crucial finding is the existence of a legal vacuum due to the absence of a specific deposit guarantee mechanism for precious metal commodities, leaving customers at the highest level of vulnerability in the event of operational failure. Therefore, this research concludes that the government should immediately formulate a regulation guaranteeing gold commodity deposits. Furthermore, the corporate entity is obligated to implement the transparency obligation of periodic gold reserve audits, which must be accompanied by enhanced public financial literacy to ensure the sustainability of an equitable investment ecosystem.